Clinical Role of Swept Source Anterior Segment Optical Coherence Tomography in Strabismus Re-Operation with Lost Surgical Details - Pujari A (Dove Medical Press, 2021)
Amar Pujari, Sujeeth Modaboyina, Deepsekhar Das, Asmita Mahajan, Rajeswari Thangavel, Swati Phuljhele, Rohit Saxena, Namrata Sharma, Pradeep Sharma Dr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, New Delhi, IndiaCorrespondence: Amar PujariDr. Rajendra Prasad Centre for Ophthalmic Sciences, All India Institute of Medical Sciences, Room No. 212, RPC-1, AIIMS, New Delhi, IndiaTel +91 8447226221Email dramarpujari@gmail.comBackground: To characterize the diagnostic role of swept source anterior segment optical coherence tomography (SS-ASOCT) in strabismus re-operations with lost surgical details.Methods: Patients presenting to our outpatient services for strabismus care from February 2020 to March 15th 2021 were systematically evaluated. Those willing to undergo re-operation were included in the study. A total of 30 patients were identified and out of this a total of 10 eyes of 10 patients with lost surgical details were finally included in the study. Demographic details, preoperative deviation, ocular findings, orthoptic measurements, detailed SS-ASOCT findings, intraoperative measurements, and post-operative outcomes were recorded.Results: The mean age of 10 patients was 23.7± 5.75 years. Seven were male and three were female. The mean pre-operative SS-ASOCT measured distance from angle to insertion was 8.90± 1.85 mm and the mean intraoperative distance was 9.12± 2.14 mm. A mean difference of 0.21± 1.31 mm was noted, and this difference was statistically insignificant (paired t test, p = 0.57). In addition, SS-ASOCT unraveled novel signs to differentiate operated eyes from the un-operated eyes, and recessed muscle from the resected muscle.Conclusion: In strabismus re-operation with lost surgical details, the pre-operative SS-ASOCT can provide reliable muscle details with respect to its type of surgery and amount surgery.Keywords: extraocular muscle, swept source anterior segment optical coherence tomography and strabismus re-operation